Amlodipine rescues advanced iron overload cardiomyopathy in hemojuvelin knockout murine model: Clinical implications - Zhabyeyev, Pavel; Sadasivan, Chandu; Shah, Saumya; Wang, Faqi; Oudit, Gavin Y. (Frontiers in Cardiovascular Medicine, 2023)
Background Iron overload cardiomyopathy (IOC) is a major co-morbidity of genetic hemochromatosis and secondary iron overload with limited therapeutic options. We aim to investigate mechanisms of rescue action of amlodipine in the murine model of iron overload, characterize changes in human cardiac tissue due to IOC, and compare them to the changes in the animal model of IOC. Methods and results As an animal model, we used male hemojuvelin knockout (HJVKO) mice, which lacked hemojuvelin (a co-receptor protein for hepcidin expression). The mice were fed a high-iron diet from 4 weeks to 1 year of age. As a rescue, iron-fed mice received the Ca2+ channel blocker, amlodipine, from 9 to 12 months. Iron overload resulted in systolic and diastolic dysfunctions and changes in the cardiac tissue similar to the changes in the explanted human heart with IOC. An IOC patient (β-thalassemia) with left-ventricular ejection fraction (LVEF) 25% underwent heart transplantation. The murine model and the explanted heart showed intra-myocyte iron deposition, fibrosis, hypertrophy, oxidative stress, remodeling of Ca2+ cycling proteins, and metabolic kinases typical of heart failure. Single-myocyte contractility and Ca2+ release were diminished in the murine model. The amlodipine-treated group exhibited normalization of cellular function and reversed fibrosis, hypertrophy, oxidative stress, and metabolic remodeling. We also report a clinical case of primary hemochromatosis successfully treated with amlodipine. Conclusions The aged HJVKO murine model on the iron-rich diet reproduced many features of the human case of IOC. The use of amlodipine in the murine model and clinical case reversed IOC remodeling, demonstrating that amlodipine is effective adjuvant therapy for IOC.